Oral Health Education to Improve Literacy and Oral Care Practices Among Older Adults in Boro Village, Sidoarjo Regency - Dwi Wahyu Indrawati; Anis Khoirin Hayati; Novita Pratiwi; Nurul Maulidah; Faisal Hamdi; Dedi Fardiaz (FKM UIN Sumatera Utara Medan, 2026)
The decline in oral health among the elderly remains a persistent community issue, primarily influenced by limited health literacy, reduced motor abilities, and a lack of regular preventive care. This community service program focused on improving oral health literacy and promoting proper daily oral hygiene practices among older adults through targeted educational interventions. The purpose of this activity was to enhance participants' understanding of common oral problems in aging, including dental caries, periodontal disease, and denture-related conditions, as well as to strengthen their skills in performing effective and safe oral care at home. The program employed an interactive approach consisting of health education sessions, visual demonstrations of toothbrushing and denture-cleaning techniques, and guided practice with direct supervision. Additional supporting materials were provided to reinforce learning retention. The results of the program indicated a noticeable increase in participants' knowledge, greater confidence in performing oral hygiene independently, and improved awareness of the importance of routine dental check-ups. Participants also reported better understanding of the relationship between systemic conditions-such as diabetes and hypertension-and oral health status. In conclusion, this community engagement activity effectively improved oral health literacy and encouraged better oral care behaviors among the elderly. Sustained implementation of periodic education, collaboration with community health cadres, and integration of oral health promotion into routine elderly health services are recommended to support longterm improvements in oral health and overall well-being.